2011
DOI: 10.1186/1475-2875-10-25
|View full text |Cite
|
Sign up to set email alerts
|

School-based surveys of malaria in Oromia Regional State, Ethiopia: a rapid survey method for malaria in low transmission settings

Abstract: BackgroundIn Ethiopia, malaria transmission is seasonal and unstable, with both Plasmodium falciparum and Plasmodium vivax endemic. Such spatial and temporal clustering of malaria only serves to underscore the importance of regularly collecting up-to-date malaria surveillance data to inform decision-making in malaria control. Cross-sectional school-based malaria surveys were conducted across Oromia Regional State to generate up-to-date data for planning malaria control interventions, as well as monitoring and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 46 publications
3
70
1
1
Order By: Relevance
“…vivax . While this finding is out of line with the literature and large-scale evaluation research, lack of protection from net use has been reported in observational studies in Ethiopia before [28-31]. In this context, these results could derive from a combination of factors including the prevalence of old and ineffective nets, the epidemiology of P .…”
Section: Discussionsupporting
confidence: 76%
“…vivax . While this finding is out of line with the literature and large-scale evaluation research, lack of protection from net use has been reported in observational studies in Ethiopia before [28-31]. In this context, these results could derive from a combination of factors including the prevalence of old and ineffective nets, the epidemiology of P .…”
Section: Discussionsupporting
confidence: 76%
“…The sampling designs and survey procedures are detailed elsewhere [17, 18]. In brief, schools were selected to provide a representative sample of malaria endemicity in each setting.…”
Section: Methodsmentioning
confidence: 99%
“…In other countries, e.g. The Democratic Republic of Congo [9] and Ethiopia [16], school surveys provided information on the malaria geographical heterogeneity and helped identifying clusters of transmission. Their representativeness, as compared to the whole community, will obviously depend on the degree of school attendance.…”
Section: Introductionmentioning
confidence: 99%